Significance of regional media in political communication of municipality´ representatives with the public. Case study - Višňovský, Ján; Obertová, Erika; Baláž, Martin (Political Preferences, 2016)
Regional and local print and electronic media in Slovakia achieved the significant development since the 90s of the 20th century. Paradoxically, relevant attention is not yet devoted to the question of media operating in the territory of a village or a region in context of regional political communication in Slovakia. Regional and local media are important communication factors in a relation local politics – media – the public although they fulfill other functions as well. The aim of this research was to prove the application of regional and local media as effective tool for creation of desired image of municipality´s representatives in the essential part of the public through the exhibition of the display of the selected media effects in relation local media – local audience. This research maps political communication of the representatives of Slovak town Žiar nad Hronom by means of contents analysis published in Mestské noviny Žiar nad Hronom. It concentrates on frequency of display of the public representatives and the recipient´s understanding of their importance as well as establishing the themes that city management considers to be priority. It is assumed that systematically and strategically directed communication through the local newspapers can maintain popularity of actual political representation and form desirable media image of its political representatives. Key words: agenda setting, local and regional media, media image, political communication, framing, Mestské noviny Žiar nad Hronom